Civil Aircraft Emissions Study and Pollutant Forecasting at a Brazilian Airport - D. A. Pamplona (Engineering, Technology & Applied Science Research, 2020)
In recent decades, the emissions of air transport industry pollutants and their impact on human health attract increased focus. The continued growth of air traffic and public awareness has transformed this field into one of the most important topics of commercial aviation. In the next 20 years, the estimated global demand for air transport will grow by an average of 5%. One of the direct consequences would be the increase in emissions, affecting significantly the communities around airports. The aim of this paper is to present an econometric model forecast of pollutant emissions generated by domestic flights in Salvador Airport. This model includes a derivative study of demand until the year 2020, considering the number of flights and emissions generated in the takeoff and landing cycles. Results present a predictive model for the number of pollutant emissions.